2016
DOI: 10.1097/gme.0000000000000690
|View full text |Cite
|
Sign up to set email alerts
|

The usability of a WeChat-based electronic questionnaire for collecting participant-reported data in female pelvic floor disorders: a comparison with the traditional paper-administered format

Abstract: WeChat-based questionnaires were well accepted by women with pelvic floor disorders and had good data quality and reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 15 publications
7
29
0
Order By: Relevance
“…Having ignored those deficiencies, we thought that the internet was more convenient and acceptable to the public, and can enable information collection working in a relatively low-cost and large-scale manner [17]. Some researchers have found higher response rates in the survey using an online questionnaire when compared to paper questionnaire [18,19]. The result of our study also showed the same trend (60.7% in the online distributed questionnaire).…”
Section: Discussionsupporting
confidence: 74%
“…Having ignored those deficiencies, we thought that the internet was more convenient and acceptable to the public, and can enable information collection working in a relatively low-cost and large-scale manner [17]. Some researchers have found higher response rates in the survey using an online questionnaire when compared to paper questionnaire [18,19]. The result of our study also showed the same trend (60.7% in the online distributed questionnaire).…”
Section: Discussionsupporting
confidence: 74%
“…WeChat is one of the fastest growing mobile apps in China, with over 697 million currently active user accounts according to a report by Tencent Inc. , who provided the WeChat platform, and it is the most popular platform visited daily by university students in China . Every student in Tongji University School of Medicine uses WeChat according to our findings, so we can take advantage of WeChat instead of developing high‐cost teaching apps.…”
Section: Introductionmentioning
confidence: 80%
“…The researchers distributed the uniform online questionnaires by WeChat, which is one of the most prevalent social software in mainland China [35,65]. Evidence supports that WeChat is an adequate platform to distribute energy-saving questionnaires or interventions [66,67]. The research team offered vouchers to all participants who successfully complete the questionnaire and provide valid feedback.…”
Section: Measurementioning
confidence: 99%